JUAL BELI EMAS SECARA TIDAK TUNAI - Susilawati, Nilda (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2017)
Buying and selling gold in cash is a golden treasure transfer contract from someone to someone else who is done by cash or credit. the purpose of this study is to analyze the system of indirect buying and selling that occurs in society today. this research includes the type of descriptive qualitative research, by reviewing various literature literature and criticize existing problems in the field If the contract of sale and sale is done not cash in the context of gold as currency, then the sale and purchase law is forbidden because it contains elements of usury, and should only be traded gold when the contract is in cash and equal in value but if the status of gold as a commodity then the sale and purchase of gold is not cash law mubah.Keywords: Jual beli emas, tidak tunai